2021
DOI: 10.1021/acs.jcim.1c00664
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Protein–Glycosaminoglycan Complexes: Does the Size Matter?

Abstract: Docking glycosaminoglycans (GAGs) has been challenging because of the complex nature of these long periodic linear and negatively charged polysaccharides. Although standard docking tools like Autodock3 are successful when docking GAGs up to hexameric length, they experience challenges to properly dock longer GAGs. Similar limitations concern other docking approaches typically developed for docking ligands of limited size to proteins. At the same time, most of more advanced docking approaches are challenging fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In fact, recent studies on large number of GAG disaccharides have further confirmed the classic works by Mulloy and co-workers [31] that glycosidic torsions Φ and Ψ vary within a relatively small range irrespective of sulfation pattern [39] , [40] . This gives rise to the canonical ‘helical’ topology of Hp/HS chains, which is used as the primary Hp/HS topology in docking [41] , [42] , [43] , although pucker and glycosidic bond flexibility is typically allowed in these studies [44] , [45] . Yet, Hp/HS chains are thought to be linear cylinders, which implies that “sulfation code” is wholly configurational with only a marginal room for IdoA conformations.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, recent studies on large number of GAG disaccharides have further confirmed the classic works by Mulloy and co-workers [31] that glycosidic torsions Φ and Ψ vary within a relatively small range irrespective of sulfation pattern [39] , [40] . This gives rise to the canonical ‘helical’ topology of Hp/HS chains, which is used as the primary Hp/HS topology in docking [41] , [42] , [43] , although pucker and glycosidic bond flexibility is typically allowed in these studies [44] , [45] . Yet, Hp/HS chains are thought to be linear cylinders, which implies that “sulfation code” is wholly configurational with only a marginal room for IdoA conformations.…”
Section: Resultsmentioning
confidence: 99%
“…The favorable flexibility parameters of the heparin chains and their high charge density suggest that the “wrap-around” mode of PF4/heparin interactions is favored thermodynamically, which is also confirmed by the results of MD simulations ( Figure 3 ). Although the MD simulations carried out in this study were not intended to explore the entire conformational space available to PF4/heparin complexes (explicit modeling remains problematic for GAG chains above decamers 28,36,37 ), they certainly demonstrate that the “wrap-around” mode of association is feasible. At the same time, one must also consider a possibility of kinetic effects preventing formation of structures that maximize the electrostatics-driven enthalpic gains.…”
Section: Discussionmentioning
confidence: 99%
“…It represents a substantial limitation in translating the results of the computational prediction to biological processes at larger scales. 127 Experimentally, this limitation is mainly due to the lack of available well-characterized longer oligosaccharides and full-length GAGs and the subsequent limitation of 3D structures of GAG–proteins complexes (currently more than 120 PDB entries, including less than 40 nonredundant nonenzymatic complexes). 110 Computational methods to tackle long polysaccharide chains are deficient because running MD simulations for many sequences remains challenging, especially at a high-throughput level.…”
Section: Protein-glycosaminoglycan Interactionsmentioning
confidence: 99%
“…About 90% of the studies have been performed with short GAG oligosaccharides (< DP5). It represents a substantial limitation in translating the results of the computational prediction to biological processes at larger scales . Experimentally, this limitation is mainly due to the lack of available well-characterized longer oligosaccharides and full-length GAGs and the subsequent limitation of 3D structures of GAG–proteins complexes (currently more than 120 PDB entries, including less than 40 nonredundant nonenzymatic complexes) .…”
Section: Protein-glycosaminoglycan Interactionsmentioning
confidence: 99%